Archaeological heritage - Rahman, Shah Sufi Mostafizur, 1964-; Asiatic Society of Bangladesh; Cultural Survey of Bangladesh Project (Dhaka : Asiatic Society of Bangladesh, 2007)
Contributed articles published under the Cultural Survey of Bangladesh Project.
Includes bibliographical references and index.
00026326
Keywords: Bangladesh -- Antiquities; Excavations (Archaeology) -- Bangladesh